2017
DOI: 10.1042/bcj20170239
|View full text |Cite
|
Sign up to set email alerts
|

Sialylated glycosylphosphatidylinositols suppress the production of toxic amyloid-β oligomers

Abstract: The production of amyloid-β (Aβ) is a key factor driving pathogenesis in Alzheimer's disease (AD). Increasing concentrations of soluble Aβ oligomers within the brain lead to synapse degeneration and the progressive dementia characteristic of AD. Since Aβ exists in both disease-relevant (toxic) and non-toxic forms, the factors that affected the release of toxic Aβ were studied in a cell model. 7PA2 cells expressing the human amyloid precursor protein released Aβ oligomers that caused synapse damage when incubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…When apoE4 residues 166-299 were removed, the ability of apoE4 to remove A␤ was significantly decreased, resulting in intracellular A␤42 accumulation [42]. Studies of A␤ have shown that the binding to sialic acids reduces A␤ cell toxicity [43][44][45]. Taken together with the current findings that apoE4 is the least glycosylated isoform, especially in CSF, it is speculated that reduced glyco-sylation/sialylation of apoE4 could result in reduced binding to A␤, which in turn could lead to a reduced ability to remove the deposited A␤ plaques.…”
Section: Apoe Isoform-specific Glycosylation Levels In Plasma and Csfmentioning
confidence: 99%
“…When apoE4 residues 166-299 were removed, the ability of apoE4 to remove A␤ was significantly decreased, resulting in intracellular A␤42 accumulation [42]. Studies of A␤ have shown that the binding to sialic acids reduces A␤ cell toxicity [43][44][45]. Taken together with the current findings that apoE4 is the least glycosylated isoform, especially in CSF, it is speculated that reduced glyco-sylation/sialylation of apoE4 could result in reduced binding to A␤, which in turn could lead to a reduced ability to remove the deposited A␤ plaques.…”
Section: Apoe Isoform-specific Glycosylation Levels In Plasma and Csfmentioning
confidence: 99%